ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSIAPAN IMPLEMENTASI PP NOMOR 12 TAHUN 2019 DI KOTA PEKANBARU - Joshua Joshua; Azlina Nur; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the influence of human resource competence, organizational commitment, information technology, availability of infrastructure and the availability of incentives on the preparation for the implementation of PP number 12 of 2019 in Pekanbaru City. The population in this study were all Regional Apparatus Organizations in Pekanbaru City, amounting to 45 OPD. The sampling method used in this study was saturated samples. The data source of this research is primary data using a research instrument in the form of a questionnaire distributed to 180 respondents. The data analysis technique used in this research is descriptive statistics and multiple linear regression analysis. The results of this study indicate that human resource competence, organizational commitment, information technology, availability of infrastructure and availability of incentives affect the preparation for the implementation of PP number 12 of 2019.Keywords: Human Resources Competence, Organizational Commitment, Information Technology, Incentive Availability, Infrastructure Availability, Implementation of Government Regulation Number 12 of 2019